The Influence of Motivation, Employee Engagement and Work Spirituality on Employee Performance at PT. Citra Anugrah Jaya - Nur, Neng Kamaliyah; Sakti, Intan Widuri (Fakultas Ekonomi Universitas Garut, 2024)
This research was conducted with the aim of obtaining the results of a study of Motivation, Employee Engagement, work spirituality and employee performance at PT. Citra Anugrah Jaya and to get an analysis of Motivation, Employee Involvement, Work Spirituality and Employee Performance at PT. Anugrah Jaya Image. This research method uses the Descriptive Verification method with multiple regression analysis. Descriptive analysis was processed using Microsoft Excel and Multiple Regression Analysis with SPSS. With sample 50 people. The research results show that there is an influence between motivation and employee performance at PT. Citra Anugrah Jaya with an influence of 41% with a correlation value of 0.596. Furthermore, employee engagement has on employee performance at PT. Citra Anugrah with an influence of 16% and a correlation value of 0.199 for work spirituality has an influence on employee performance with an influence of 43% and a correlation value of 0.264. This shows that the partial influence of work motivation and spirituality has an effect on employee performance while work engagement has no effect on employee performance. The residual factor in this study that was not examined was 62%, so this shows that there are other factors that can influence the performance of PT employees. The Image of Grace.